Analisis Kegiatan Koreksi dan Validasi terhadap keputusan persetujuan pendaftaran tenaga Kerja di BPJS Ketenagakerjaan Cabang Juanda - Syafitra, Awaliya Rahmadhani; Kusuma, Yanda Bara (Jurnal Bisnis Indonesia, 2024)
This research is conducted to understand how the Analysis of Correction and Validation Activities influences the decision for the approval of employee registration at BPJS Employment. The type of research employed is a qualitative research method. The research technique involves interviewing staff at the Juanda branch of BPJS Employment. The results of this study indicate that the correction and validation process of labor data significantly impacts the performance of the BPJS Employment company. Correction and validation activities for labor data are carried out in small, medium, and large-scale companies. It is crucial to enhance these correction and validation activities to ensure the efficient completion of the employee registration approval process.Keywords: Correction, Validation, Labor, Registration Approval